An experimentally validated model for predicting the tensile modulus of tubular biaxial and triaxial hybrid braids. Issue 12 (1st October 2022) - Ghamkhar, Ghazal; Johari, Majid Safar; Toudeshky, Hossein Hosseini; Bodaghi, Mahdi
Abstract: Braiding is a versatile and cost‐effective approach to generating various composite structures for mechanical, sports, and biomedical engineering applications, which are different from each other. For example, a stent is a braided structure and blood penetration in it is essential as much as the right function. Predicting the tensile responses is a prerequisite for the success of implementation of braided structures, and it is usually performed via destructive mechanical testing that might be costly and/or time‐consuming. Therefore, it is essential to provide a model that can accurately predict the tensile modulus. In this research, a theoretical model is developed using the simplification of a braided structure and is validated via testing of biaxial and triaxial braids composed of polyester, glass, and basalt yarns on a 16‐carrier vertical braiding machine. Experimental results not only are used for the model validation but also show the effectiveness of axial yarn presence, hybridization, and the presence of high‐performance yarn in the braided structures on the tensile properties. A good correlation between theoretical values and experimental results is observed approving the high accuracy of the proposed model. This paper is likely to fill a gap in the state of the art and provide pertinent results that are instrumental in the design of hybrid‐braided structures with minimum computational/experimental effort. The research innovation centers on the use of two different yarns to make hybridization, simplicity of the model to be used for biaxial and triaxial braided structures, and a start to omit destructive tests. Abstract :